LEXICAL METAPHOR IN PRINTED CAR ADVERTISEMENTS - Misdiana Misdiana; Amrin Saragih; Siti Aisyah Ginting (Universitas Negeri Medan, 2019)
This study deals with the use of Lexical Metaphor in Printed Car Advertisements. The objective of the study was to describe the types of lexical Metaphor used in Printed Car Advertisements and to elaborate the reasons why those kinds of lexical metaphor used in that way. This study was conducted by using descriptive qualitative research. The source of data was taken from slogan of magazines and brochure which containing 28 texts printed. The data were analyze using content analysis technique by describing the kinds of lexical metaphors. The data obtained through purposive sampling technique with focused on the lexis (words) that contained of lexical metaphors., the realization of lexical metaphor and the reason were analyzed by using systematic functional linguistic approach. The instrument in this study was the researcher itself. The result showed that there are eight concepts of lexical metaphor, namely Noun-Noun, Noun-Verb, Noun Adjective, Intransitive-Verb, Adjective-Adjective, Intransitive_Verb-Noun, Noun-Pronuon, Verb_Pronoun. The findings showed that advertisers construct different slogan for persuading the consumers or to positively dispose toward their brand. As a form of marketing strategy, advertising ideology work and it played an important role to beautify or describe his literature, feeling and thought. Potentially to make specific product or brand name more appealing and memorable. The reason were attention getting, persuasion, innovation and creativity, prestige, technological words, to fun and memo ability cause the owner thought that tag line/branding cannot translate directly in English the message cannot deliver well consumers because English has own term in the market/business.Keywords: Metaphor, Printed advertisement, Lexical.